(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To assess early functional outcome of total hip arthroplasty for displaced femoral neck fractures. Methods: This clinical trial study conducted in Jinnah Hospital Lahore Orthopaedic unit 2 from August 2015 to October 2017. Eighty-five patients with displaced femoral neck fractures were managed by cemented primary total hip arthroplasty. We included otherwise physically and mentally healthy patients who were community ambulators of the age group ranging from 55 to 80 years with an average age of 62.37 years. All the patients with infection, nonunion, pre-existing rheumatoid arthritis and pathological fractures were excluded from the study. A modified Hardinge approach was used in all patients and cemented total hip prosthesis was used. Every patient received pre-operative, intra operative and post-operative antibiotic regime. Low molecular weight heparin was administered prophylactically. All the patients underwent specific rehabilitation protocol and mobilized on the first post-operative day. Functional outcome in all patients was evaluated in terms of harris hip score (HHS) after six weeks, 3 months and 6 months Paired t test was used to assess difference between means HSS at 3 weeks and 6 months for statistical significance with p < .05. Results: 57.6% (49) males and 42.4% (36) females with a mean age of 62.37 + 28.42 years ranging from 55 to 80 years were studied. A total of 45.9% (39) patients were operated on right and 54.1% (46) operated of left hips. The mean Harris hip score at six weeks was 78.117 + 5.757, at three months was 83.5294 + 5.785, and at six months was 88.600. + 4.746 (P< .000). Conclusion: Total hip replacement has a good functional outcome in displaced femoral neck fractures in otherwise healthy and lucid patients. On basis of better functional scores in our results we can infer that cemented total hip replacement offers early return to function so this procedure is suggested in elderly active patients with femoral neck fracture.